Why Is an Early Start of Training Related to Musical Skills in Adulthood? A Genetically Informative Study - Wesseldijk, Laura W.; Mosing, Miriam A.; Ullén, Fredrik (Psychological science, 2021)
Experts in domains such as music or sports often start training early. It has been suggested that this may reflect a sensitive period in childhood for skill acquisition. However, it could be that familial factors (e.g., genetics) contribute to the association. Here, we examined the effect of age of onset of musical training on musical aptitude and achievement in professional musicians (n = 310) and twins (n = 7,786). In line with previous literature, results showed that an earlier age of onset was associated with higher aptitude and achievement in both samples. After we adjusted for lifetime practice hours, age of onset was associated only with aptitude (p < .001; achievement: p > .14). Twin analyses showed that the association with aptitude was fully explained by familial factors. Thus, these findings provide little support for a sensitive period for music but highlight that familiar factors play an important role for associations between age of onset of training and skills in adulthood.